Flow Field Analysis of Gas Injection and Brine Discharge in Natural Gas Storage Salt Cavern. Issue 1 (1st June 2022) - Zhang, Yi; Huang, Wei; Cen, Xueqi; Zhao, Dandi; Chai, Guoxing
Abstract: Gas injection and brine discharge is the key link in the construction and safe operation of the salt cavern gas storage. Accurate description of the bottom flow field of the salt cavern in the process of gas injection and brine extraction is the basis and premise for determining the depth of the brine drainage string. According to the characteristics of gas injection and brine discharge, a numerical simulation calculation model of the brine flow field near the inlet of the brine discharge tubing was established. The brine flow field under different working conditions is simulated, and the safe brine drainage rate at different residual brine depths in the later stage of gas injection and brine drainage is determined, which provides technical support for the adjustment of gas injection brine drainage rate in the later stage of construction.